Humanistic quality teaching reform of material science - Ma Zhuang; Cheng Zhifang; Gao Lihong; Zhang Hongmei (SHS Web of Conferences, 2023)
How to play the role of humanistic quality education in Material major courses? This paper discusses the design ideas and specific implementation methods of integrating Curriculum humanistic quality into the teaching of material science from three aspects: curriculum knowledge objectives and ability objective, strategies of curriculum teaching methods, course expected learning results. After humanistic quality teaching reform of the basic course of material science, professional knowledge points and ideological and political elements are integrated, and the teaching platform, students' real feelings and the power of humanistic quality elements are coordinated.